Asymptomatic hypertension-mediated organ damage in patients with or without moderate to severe chronic kidney disease. (25th November 2020) - Schiavone, M; Gobbi, C; Ratti, A; Ferrari, G; Villarini, A; Meazza, R
Abstract: Introduction: Moderate or severe chronic kidney disease (CKD) is regarded as high or very high risk factor in the Systematic COronary Risk Evaluation (SCORE) system, as stated in the ESC guidelines on arterial hypertension. Assessment of cardiovascular (CV) risk should be completed evaluating hypertension-mediated organ damage (HMOD). Purpose: The aim of our study was to find out differences in HMOD in patients with or without moderate to severe chronic kidney disease (CKD). Methods: We enrolled 80 consecutive non-diabetic hypertensive patients, divided into two groups according to the presence of impaired renal function, evaluated by estimated glomerular filtration rate (eGFR): moderate to severe CKD group (n=26 patients, eGFR <60 mL/min/1.73 m 2 ) and mild CKD - normal renal function group (n=54 patients, eGFR ≥60 mL/min/1.73 m 2 ). A transthoracic echocardiogram was performed to evaluate cardiac HMOD. Small and large vessel damage was assessed by means of non-mydriatic digital fundus oculi examination in order to detect arteriolar narrowing using arteriolar-venular ratio (AVr), applanation tonometry to measure carotid-femoral pulse wave velocity (cfPWV) and carotid ultrasound to quantify intima-media tickness (IMT). Results: Moderate to severe CKD patients appeared to be older (mean age 75.54±8.06 vs 63.38±9.62, p=0.001) and showed lower level of total and LDL cholesterol. Both groups showed abnormal values of cfPWV, but these were significantly higher in the presence of moderate to severe CKD (14.12±7.93 m/s vs 10.94±5.81 m/s, p=0.03). Abnormal AVr values were found in patients with higher grade of CKD, with statistically significant differences in the two groups (0.75±0.015 vs 0.81±0.06, p=0.00001). Carotid IMT resulted to be at the upper limit of normality in both groups (0.95±0.15 vs 0.90±0.18, p=0.35). With regard to echocardiography evaluation, left ventricular mass index (LVMi: 105.04±0.4 vs 96.35±1.7, p=0.06) and relative wall thickness (RWT: 0.43±0.02 vs 0.42±0.05, p=0.41) did not differ significantly in the two groups, with a mild trend for LVMi. Both groups showed abnormal diastolic dysfunction on average, but no differences emerged in the presence of more severe renal impairment (deceleration time 281.74±0.37 vs 256.30±0.54, p=0.08; E/A 0.86±0.03 vs 0.95±0.25, p=0.20; E/e' 7.89±2.93 vs 7.60±2.46, p=0.66). Conclusions: Our study showed significant differences in HMOD in presence of moderate to severe renal impairment. Moderate to severe CKD seemed to be associated to vascular damage (hypertensive retinopathy and arterial stiffness), while no significant differences in echocardiographic markers of cardiac remodeling were found, suggesting that systemic vascular damage is more closely linked to CKD than cardiac damage. Therefore, the use of fundus oculi examination and PWV should always be considered to properly assess the target organ damage in hypertensive patients with CKD. Funding Acknowledgement: Type of funding source: None